(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article aims to thoroughly explore the theoretical foundations of eco-aesthetics, its origins, relevance, and conceptual meaning. It discusses the similarities and differences between eco-aesthetics and environmental education. The historical emergence and current roles of eco-aesthetics are outlined, along with several methods and recommendations for developing eco-aesthetic competence in primary school students.